Cluster headache: review of current understandings - Ribeiro, Reinaldo Teixeira (2012)
Cluster headache (CH) is the trigeminal autonomic cephalalgia whose pain is considered to be one of the most severe known to man. Although diagnosed less frequently than migraine and tension-type headaches, CH is nonetheless an important clinical entity, particularly given our evolving understanding of its actual epidemiology, pathophysiology, current diagnostic criteria and treatment approaches. We carried out a systematic review through the United States National Library of Medicine (PUBMED) by using the search term "cluster headache" and the results were narrowed to manuscripts published in the last ten years with subsequent reference searches and verification of source data. This article presents a review of the current understanding of the most important aspects of CH, with emphasis on mechanisms and treatment approaches.